Insect population control using female specific pro-drug activation. - Markaki, M.; Craig, R.K.; Savakis, C. (Insect Biochemistry and Molecular Biology, 2004)
A system for population control of insects is proposed. It is based on transgenic insects expressing an enzyme which converts an inactive pro-drug into an active, toxic form. A model system is presented which relies on transposon-mediated integration of a bacterial cytosine deaminase (CD) gene into the genome of Drosophila melanogaster. We demonstrate female-specific sterility and transgene-dependent lethality when flies carrying the CD gene under a Drosophila female-specific promoter/enhancer are treated with 5-Fluorocytosine, a low-toxicity nucleoside analogue which is converted to toxic 5-Fluorouracil by the enzyme. The approach can be used with existing pro-insecticides and appropriate converting enzymes in combination with established mass rearing technology, for targeted, environmentally acceptable control of insects of economic and public health importance.